2020
DOI: 10.1039/c9sc06226b
|View full text |Cite
|
Sign up to set email alerts
|

In vivomonitoring of tissue regeneration using a ratiometric lysosomal AIE probe

Abstract: An AIE-active ratiometric probe for the first time achieved the long-term quantification of lysosomal pH during the medaka larva's caudal fin regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 85 publications
(94 reference statements)
0
61
0
Order By: Relevance
“…Recently, in 2020 the Tang group proposed an AIE lysosome targeting probe for monitoring lysosomal pH during the tissue regeneration process. 115 Lysosomes play a key role in tissue regeneration, for which pH 4–5 is essential for lysosomal hydrolase activity. Whilst research has been conducted on lysosomes and tissue regeneration, an in vivo study of lysosome pH during the regeneration process had not previously been reported.…”
Section: Multiple Modality Fluorescent Probesmentioning
confidence: 99%
“…Recently, in 2020 the Tang group proposed an AIE lysosome targeting probe for monitoring lysosomal pH during the tissue regeneration process. 115 Lysosomes play a key role in tissue regeneration, for which pH 4–5 is essential for lysosomal hydrolase activity. Whilst research has been conducted on lysosomes and tissue regeneration, an in vivo study of lysosome pH during the regeneration process had not previously been reported.…”
Section: Multiple Modality Fluorescent Probesmentioning
confidence: 99%
“…al recently reported the utilization of an AIEgen for imaging the tissue regeneration process. 82 In their approach, lysosome was selected as the target, due to its important roles in autophagy, a critical process involved in tissue regeneration. To track the lysosome and quantify lysosomal pH, CSMPP was designed and synthesized ( Figure 17A).…”
Section: Tissue Regeneration Visualizationmentioning
confidence: 99%
“…37,38 Due to the dynamicity of the lysosomal compartment, imaging lysosomal properties to comprehend its activities is extremely fascinating and to pursue this, numerous synthetic organic lysotrackers have been reported by various research groups. [38][39][40][41] The majority of such reported lysosome targeting probes and commercially available lysotrackers like Neutral Red (NR), DND-189, and DND-99 suffer from pHdependent fluorescence, interference from non-specific binding, background fluorescence, insufficient photostability, and cytotoxicity. 26,42,43 .…”
Section: Introductionmentioning
confidence: 99%